(untitled) (African Multidisciplinary Journal of Research, 2025)
Youth unemployment remains a critical issue across Africa, exacerbated by technological advances, labour market shifts, and economic constraints. This scoping review examines the role of digital technology in addressing youth unemployment in Africa, focusing on the development of digital skills, the role of digital platforms in entrepreneurship, and the potential for digital technology to transform key sectors. A total of 20 studies were included, spanning from 2019 to 2024, with a focus on Nigeria, South Africa, and Sub-Saharan Africa. The findings indicate that digital skills development enhances employability, with digital platforms fostering youth entrepreneurship by providing access to new markets and self-employment opportunities. However, challenges such as limited infrastructure, poor government support, and the digital divide in rural areas persist. Additionally, while digital technology offers numerous opportunities, it also poses the risk of job displacement for low-skilled workers. This review highlights gaps in the literature, including a lack of longitudinal studies and an under-exploration of emerging technologies like artificial intelligence in job creation. Policymakers should prioritize investments in digital infrastructure and inclusive education to bridge the digital divide and ensure that African youth can benefit from the digital economy.